Numerical Solution of Higher Index Nonlinear Integral Algebraic Equations of Hessenberg Type Using Discontinuous Collocation Methods - Shiri, Babak (Mathematical Modelling and Analysis, 2014)
In this paper, we deal with a system of linear and nonlinear integral algebraic equations (IAEs) of Hessenberg type. Convergence analysis of the discontinuous collocation methods is investigated for the large class of IAEs based on the new definitions. Finally, some numerical experiments are provided to support the theoretical results.